Casebook for counseling lesbian, gay, bisexual, and transgender persons and their families - Dworkin, Sari H.; Pope, Mark, 1952- (Alexandria, VA : American Counseling Association, 2012)
'This captivating book contains 31 case studies that focus on what is said and done in actual counseling sessions with LGBTQQI clients, including diagnosis; interventions, treatment goals, and outcomes; transference and countertransference issues; other multicultural considerations; and recommendations for further counseling or training. Experts in the field address topics across the areas of individual development, relationship concerns, contextual matters, and wellness. The cases presented include coming out; counseling intersex, bisexual, and transsexual clients; couples, marriage, and family counseling; parenting issues; aging; working with rural clients and African American, Native American, Latino/a, Asian, and multiracial individuals; sexual minority youth; HIV; sexual and drug addictions; binational couples; work and career; domestic violence; spirituality and religion; sexual issues; and women's health'--Provided by publisher.
Foreword / Colleen R. Logan -- Introduction / Sari H. Dworkin and Mark Pope -- Sexual Minority Youth : The Case of Donald Wilson / Suzanne M. Dugger and Laurie A. Carlson -- Coming Out for Gay Men / John F. Marszalek and Edward P. Cannon -- Counseling Strategies With Intersex Clients : A Process-Based Approach / Theodore R. Burnes and Kate Richmond -- Counseling and Advocacy With a Gay Father, a Straight Mom, and a Transgender Adolescent / Stuart F. Chen-Hayes -- Counseling Older Gay Men / Douglas Kimmel -- Counseling Older Lesbians : The Case of Pat and Selene / M. Carolyn Thomas, S. Lenoir Gillam, and Paul F. Hard -- An Asian Indian Woman's Ethnic, Sexual, and Career Identity / Hemla D. Singaravelu -- Lesbian Couples and Marriage Counseling / Colleen M. Connolly -- Desire, Love, and Shame in Gay Male Relationships : The Case of Tyler / Armand R. Cerbone -- Parenting Issues for Lesbian Couples / Susan Kashubeck-West -- A Reluctant Husband and Troubled Family / Connie Callahan and Shirley Cornett -- Counseling and Advocacy With An International/Dual National Same-Gender Couple and Family / Stuart F. Chen-Hayes -- A Therapist Expands Her Ideas About Relationships / Sari H. Dworkin -- Counseling Bisexual Clients : More Than the Sum of the Parts / Beth A. Firestein -- Working With African American Lesbian, Gay, Bisexual, Transgender, and Queer People / Ron McLean -- Native American and Gay : Two Spirits in One Human Being / Mark Pope -- 'Why Did God Make Me This Way?' The Case of a Chinese American Gay Christian Man / Terry S. Gock -- Counseling Latin Gays and Lesbians / Samuel Sanabria and Ana Puig -- Multiracial/Multiethnic Queer and Transgender Clients : Intersections of Identity and Resilience / Anneliese A. Singh and Kirstyn Yuk Sim Chun -- Transsexual Case Studies : Transition Is Not the End of the Road / Randall D. Ehrbar -- Counseling With Rural Lesbian, Gay, Bisexual, and Transgender Persons / Paul A. Datti -- Mario's Journey of Faith / Kathleen Y. Ritter and Anthony I. Terndrup -- Sex and Lesbian Women / Joy S. Whitman -- Sexual Addiction and the Gay Male Client / Brian J. Dew and Misti A. Storie -- Counseling HIV-Positive Gay Men / David W. Hart -- Moving Through the Void : Counseling Gay Men With Histories of Chemical Abuse and Dependency / A. Michael Hutchins -- The Case of Eve : A Picture of a Lesbian Health Journey / Jane E. Rheineck and Catherine B. Roland -- Sexual Orientation Conversion Therapy : Fact, Fiction, and Fraud / Douglas C. Haldeman -- Domestic Violence in Same-Sex Relationships / Connie R. Matthews and Peggy Lorah -- Using Psychological Assessment Tools With Lesbian, Gay, Bisexual, and Transgender Clients / Jeffrey P. Prince and Michael J. Potoczniak -- When the Political and the Personal Collide : Lesbian, Gay, Bisexual, and Transgender People as Political Targets / Glenda M. Russell -- Appendix A: Competencies for Counseling Gay, Lesbian, Bisexual and Transgendered (LGBT) Clients -- Appendix B: American Counseling Association Competencies for Counseling With Transgender Clients.
Includes bibliographical references.
Print version record.
Keywords: Lesbians -- Counseling of -- Case studies; Gays -- Counseling of -- Case studies; Bisexuals -- Counseling of -- Case studies; Transgender people -- Counseling of -- Case studies; Counseling -- Methodology; Bisexuals -- Counseling of -- Case studies; Counseling -- Methodology; Gays -- Counseling of -- Case studies; Lesbians -- Counseling of -- Case studies; Transgender people -- Counseling of -- Case studies; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; Electronic books